Improving Denitrification Models by Including Bacterial and Periphytic Biofilm in a Shallow Water‐Sediment System. Issue 10 (20th October 2018) - Xia, Yongqiu; She, Dongli; Zhang, Wenjuan; Liu, Zhipeng; Wu, Yonghong; Yan, Xiaoyuan
Abstract: Denitrification is one of the most challenging nitrogen (N)‐cycling processes to quantify due to complex interactions among influencing factors. In shallow water‐sediment systems, ubiquitous periphytic biofilms consisting of a consortium of algae, bacteria, and nutrients account for additional interactions. The challenge in improving denitrification models is to determine how each factor directly affects denitrification and how those factors indirectly impact denitrification via interactions with other factors. We combined incubation experiments and structural equation modeling to reveal the interaction networks of biotic and abiotic factors and their roles in net denitrification. The N species in the sediment exerted much greater control over net denitrification than that exerted by the N species in the water column. In addition, the relative abundances of denitrifier and nitrifier genes in the sediment showed a dominant control over net denitrification that was similar to the control by N species but was affected by abiotic factors. Periphytic biofilm increased net denitrification both directly and indirectly by altering the pH and the dissolved oxygen, dissolved organic carbon, and N concentrations in the water column and sediment. The overall contribution of periphytic biofilm to net denitrification was less than that of the sediment but greater than that of the water column. Our findings highlight the importance of incorporating bacterial denitrifier and nitrifier genes and periphytic biofilm characteristics during model construction when predicting denitrification in a shallow and stagnant water‐sediment system. Key Points: SEM was used to reveal the interaction networks of biotic and abiotic factors and their roles in net denitrification The periphytic biofilm increased the denitrification rate directly and indirectly We suggest improving model precision by including periphytic and bacterial factors